2014
DOI: 10.1093/europace/euu215
|View full text |Cite
|
Sign up to set email alerts
|

Contact-force guided radiofrequency vs. second-generation balloon cryotherapy for pulmonary vein isolation in patients with paroxysmal atrial fibrillation--a prospective evaluation

Abstract: Our preliminary findings suggest that CF-guided radiofrequency and cryotherapy present very similar performances in the setting of paroxysmal AF catheter ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(108 citation statements)
references
References 32 publications
4
103
1
Order By: Relevance
“…26 However, ablation of persistent AF still remains a challenge. A recent multicenter randomized controlled trial showed that catheter ablation was more effective than drug therapy as a rhythm control strategy, but almost 40% of patients presented with AF or AT relapses in the first 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, ablation of persistent AF still remains a challenge. A recent multicenter randomized controlled trial showed that catheter ablation was more effective than drug therapy as a rhythm control strategy, but almost 40% of patients presented with AF or AT relapses in the first 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in more circumferential and permanent lesions around the PV ostium [11]. More recently, the prospective studies adapting the novel Arctic Front Advance TM cryoballoon catheter have demonstrated better than 80 % freedom from AF at 12 months even when using the 28 mm balloon [11][12][13][14][15][16][17]. This improved efficacy might be associated with the upgrade of cooling uniformity in the second generation cryoballoons.…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…Traditional (point-by-point) radiofrequency catheters use thermal 1 3 energy to ablate cardiac tissue; however, more recently cryoablation has gained an increasing use in ablation and isolation of the same AF triggers. Utilizing the cryoballoon system, operators are able to employ an anatomically based balloon catheter which has demonstrated a significant efficacy with perhaps more favorable safety and efficiency [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Acutely, the time to achieve PVI has shortened and acute PV reconnection is rare, and chronically, freedom from AF seems to be higher in non-randomized studies. [10][11][12][13][14][15][16][17][18] Also, the rates of PV reconnection in patients with recurrent AF are remarkably low compared with historic controls. 19 While research has indicated consistent patient outcomes with CB2, a comprehensive report of CB2 procedural recommendations has not been published.…”
Section: Introductionmentioning
confidence: 99%